Thin‐Film Solar Cells by Silicon‐Based Nano‐Pyramid Arrays. Issue 5 (23rd February 2022) - Huang, Zhisen; Wang, Bo
Abstract: In this paper, a high‐efficiency silicon‐based thin‐film solar cell is proposed based on double‐layer nano‐pyramid (DNP) arrays. In the model, the surface and bottom of the silicon photovoltaic layer are embedded with silicon nano‐pyramid array and aluminum nano‐pyramid array, respectively. The optical and electrical parameters of the DNP solar cell are presented by using the 3D finite‐difference time‐domain (FDTD) method. The short‐circuit current density ( J sc ), integrated absorption ( α ) and photoelectric conversion efficiency ( η ) of the optimized DNP solar cell are 43.61 mA cm −2, 95.20% and 27.12%, respectively. Compared with the planar solar cell, the α and η of the DNP solar cell are increased by 45.31% and 15.77%, respectively. To investigate the performance of the proposed solar cell, the principle of light absorption enhancement is analyzed by spectrum and field strength distributions for the DNP structure. Furthermore, the carrier recombination and manufacturing of the DNP solar cell, and compared the structures of different arrays is studied. Further results show that the DNP structure has excellent light absorption and tolerance, which has positive significance for the development of silicon‐based thin‐film solar cells. Abstract : A thin‐film c‐Si solar cell is investigated in this work based on double‐layer nano‐pyramid arrays. This structure has excellent light trapping properties with an optical integrated absorption of 95.20% in the studied band. Additionally, the physical mechanism of light trapping in this solar cell and the influence of various factors on its performance are analyzed in detail.